2023
DOI: 10.1177/23259671231160296
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Graft Failure After Meniscal Allograft Transplantation: A Systematic Review and Meta-analysis

Abstract: Background: Graft failure after meniscal allograft transplantation (MAT) may necessitate revision surgery or conversion to arthroplasty. A comprehensive understanding of the risk factors for failure after MAT of the knee may facilitate more informed shared decision-making discussions before surgery and help determine whether MAT should be performed based on patient risk. Purpose: To perform a systematic review and meta-analysis of risk factors associated with graft failure after MAT of the knee. Study Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Equally improved clinical outcomes have been generally reported after MMAT and LMAT [ 15 , 32 , 37 ]. A recent systematic review found no significant risk for graft failure between patients receiving either MMAT or LMAT [ 17 ]. In most studies, MAT seems to decrease pain in the affected compartment and provides subjective improvement in up to 70% of patients [ 11 , 30 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equally improved clinical outcomes have been generally reported after MMAT and LMAT [ 15 , 32 , 37 ]. A recent systematic review found no significant risk for graft failure between patients receiving either MMAT or LMAT [ 17 ]. In most studies, MAT seems to decrease pain in the affected compartment and provides subjective improvement in up to 70% of patients [ 11 , 30 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 systematic review [27] highlighted conflicting evidence concerning the impact of chondral damage on MAT outcomes. However, a more recent extensive systematic review and meta-analysis [28] identified a pronounced association between the extent of cartilage damage at the time of MAT and subsequent graft failure. Despite these findings, only a few studies have reported outcomes after combined articular cartilage restoration and MAT, demonstrating the potential for positive results and warranting further investigation [29].…”
Section: Introductionmentioning
confidence: 99%